2023
DOI: 10.1007/s10236-023-01583-7
|View full text |Cite
|
Sign up to set email alerts
|

Link between the internal variability and the baroclinic instability in the Bohai and Yellow Sea

Lin Lin,
Hans von Storch,
Xueen Chen
et al.

Abstract: A regional ocean ensemble simulation with slightly different initial conditions demonstrates that internal variability is formed (not only) in the Bohai and Yellow Sea. In this paper, we analyze the relationship between the internal variability and the baroclinic instability, (represented by the Eady predicted theoretical diffusivity $${K}_{t}$$ K t ; the larger the $${K}_{t}$$ K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Previously it was mentioned that tidal forcing could affect the already existing eddy field, but we could also consider that it could affect the formation of eddies. Lin et al (2023) found that with tidal forcing there is an increase in vertical mixing and thus a change of stratification that decreases baroclinic instabilities. Ajayi et al (2020) showed that for the North Atlantic baroclinic mixed layer instabilities are responsible for an increase of submesoscale eddies in Winter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously it was mentioned that tidal forcing could affect the already existing eddy field, but we could also consider that it could affect the formation of eddies. Lin et al (2023) found that with tidal forcing there is an increase in vertical mixing and thus a change of stratification that decreases baroclinic instabilities. Ajayi et al (2020) showed that for the North Atlantic baroclinic mixed layer instabilities are responsible for an increase of submesoscale eddies in Winter.…”
Section: Resultsmentioning
confidence: 99%
“…Since mesoscale eddies can retain floating material for several days (e.g., d 'Ovidio et al, 2013;Condie & Condie, 2016;Limer et al, 2020;Bello-Fuentes et al, 2021), this loss of energy could imply a loss of the coherence of their structure and thus of their capacity to accumulate/trap material. One of the main mechanisms that generate coherent eddy structures, are baroclinic instabilities (Stammer, 1997), and these can be modified by tidal forcing (Lin et al, 2023). While no specific research has been done on the impact of internal waves on the retention capacity of eddies, some studies have been done with surface waves.…”
Section: Introductionmentioning
confidence: 99%
“…The model-simulated elevation, temperature, salinity, and circulation patterns were validated by Huang et al (2019) and Lin et al (2022Lin et al ( , 2023. In this study, we focus directly on the analysis and discussion of the Qingdao cold water mass.…”
Section: Model Validationmentioning
confidence: 88%
“…The model domain includes the Bohai and Yellow Sea, ranging from 31.885°N to 40.942°N and from 117.572°E to 126.915°E, respectively (Fig. 1 in Lin et al (2023)). The open boundary across the Yellow Sea extends from Qidong in China eastward to the southern tip of the Korean Peninsula, and radiation boundary conditions are used.…”
Section: Model Configurationmentioning
confidence: 99%
See 1 more Smart Citation